O quintal é minha escola: a materialidade da Pedagogia da Alternância na Escola Família Agrícola do Bico do Papagaio Padre Josimo – EFABIP - SILVA, Iara Rodrigues da (2021)
This research aims to analyze the materiality of the Pedagogy of Alternation at the Escola Família Agrícola do Bico do Papagaio Padre Josimo – EFABIP, located in the municipality of Esperantina – TO, but which serves students from 12 municipalities in the microregion of Bico do Papagaio, cartography that demarcates the meeting of the states of Tocantins, Pará and Maranhão, evidencing the implementation of the instruments that put into practice the Alternating Pedagogy. In this sense, we resorted to dialectical historical materialism and all stages of construction of the research were carried out through the action research method, which is, therefore, a qualitative approach to research in the field of Rural Education. The data collection instruments used were free interviews, participant observation and document analysis. The theoretical support is supported by Freire (1996; 2019); Arroyo (2014); Caldart (2004); Molina (2015); Gimonet (2007); Begnami (2021); Silva (2018); Oliveira (2020); and scientific productions related to the study, such as Rural Education, Pedagogy of Alternation and Agricultural Family Schools. This research aimed specifically to contribute to the training of teachers/instructors who arrive at EFABIP, developing a Pedagogical Support Booklet for the continuous use of teachers. In a context where class struggle and social exclusion prevail, the difficulties of the alternating teaching process must be considered within the limits imposed by the educational system in the state of Tocantins. Thus, under these aspects, the results point to contradictions between theory and practice in the daily life of this educational proposal, but also points to a relentless search for solutions to these problems. The research results also express the change of view of the Teachers/monitors who come to EFABIP, thus reflecting on the process of identity construction of the male and female students in the countryside, water and forest.